SAYLAWBAY JUMAǴULOV SHÍǴARMALARÍNDA QOLLANÍLǴAN FOLKLORLÍQ OBRAZLAR - Qudiyarova, R. (SCIENCE and SOCIETY, 2025)
The article focuses on the issue of folklore and humor in S. Jumagʻulov's work. In Karakalpak literature, the character of Omirbek is known as a master of funny words. It is said that the writer further improved the image of Omirbek and created his image in written literature.